PERUBAHAN RESPON PAKAN PADA IKAN MAS KOKI (Carasias auratus) DENGAN RANSANGAN WARNA LAMPU - Erlangga Erlangga; Riri Ezraneti; Mawardi Mawardi (Berkala Perikanan Terubuk, 2017)
Goldfish have promising prospects of aquaculture development in the field of ornamental fish, because it have attractive colours and very easily cultivated. The main thing in the growth of goldfish is feed by increasing appetite goldfish, this fish are fototaxis, so to the stimulate of fish feeding can be manipulation with environment on different light color light. The methods of this research was rared fish with different colours, the treatments were rared fish with yellow light (A), green light (B), red light (C) and Control (D). The results of the study showed significant differences in increased appetite goldfish rared on the red light (C) were have high respons with feed and (16.145seconds) and the higest growth of the weight (1, 26 gram).